Experimental Research on the Insulation Effect of Water-retaining Roof Bricks in Transition Season. (2015) - Qing, Yutao; Wang, Ling; Xu, Zhimao; Han, Rubing; Long, Enshen
Abstract: The roof, as an important part of the building external envelope, has a significant impact on top floor rooms' indoor energy consumption and thermal comfort. A roof pond is a special system that can be used for passive cooling buildings during summer. Three experiments were carried out to test the insulation effect of water-retaining roof bricks under natural climatic conditions. It was concluded that water-retaining roof bricks have heat insulation effect. A brick model 300 mm x 300 mm x 240 mm was found to be most effective. The bricks were beneficial for indoor heat dissipation. This research helps to understand the heat and mass transfer mechanism and energy consumption characteristics of different roof structures. It can contribute to the design of a better thermal-performance water roof and energy efficient buildings in sub-tropical climatic conditions.